ماحولیاتی و موسمیاتی تغیرات سے متعلق عوامی ذمہ داریاں اور آگہی ( سیرت النبیﷺ کی روشنی میں): Public Responsibilities and Awareness Regarding the Environmental and Climate Changes (In the light of the Prophet’s life) - Abbas, Yasir; Hussain, Malik Akhtar; Shahid, Muaaz (Al-Amīr Research Journal for Islamic Studies, 2023)
Allah has made the man as his caliph on earth and created the natural resources of the universe for the sake of human beings. Due to advancement of industrialization the natural resources and environment have been threatened while the environmental pollution has become an international challenge in modern times. Some of the guiding principles mentioned in the Sirat-un-Nabiﷺ are helpful in basic guidance of humanity, such as the prohibition of extravagance and oppression, the gratitude for divine blessings, the observance of the rights of worship, and so on. However, there are certain rules and decrees that provide specific guidelines for the protection and proper use of certain natural resources, such as water, trees, agriculture, forests, wind, etc. That some of them have been ordered to perform their duties, Such as the commands to plant trees, to keep water clean, to cultivate, to raise animals and to be gentle with them, etc. Such as prohibitions of cutting down trees unnecessarily, of polluting water, of spoiling fields, and the prohibition of cruelty to animals, etc. In this study, these demands have been explained in some detail in the light of Quran and Hadiths. Key Words: Environment, Pollution, Responsibilities, Sirat -un-Nabiﷺ